Topological structure difference between isometric strength and rate of force development in elite youth female team handball players - Petronijevic, M.; Dopsaj, M.; Valdevit, Z. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
This study aimed to investigate differences in the topological structure of muscle groups with different contractile characteristics (isometric strength and rate of force development) among youth elite female handball players. Thirty-two players from the Serbian Youth National Team (age: 16.8 ± 0.9 yrs., BH: 173.5 ± 5.9 cm, BM: 70.6 ± 7.6 kg, and BMI: 23.41 ± 1.89 kg/m2) underwent assessment with five individual tests: isometric right hand grip (iHG_R), isometric left hand grip (iHG_L), isometric dead lift (iDL), isometric standing leg extension (iLE) and isometric bilateral ankle extension (iAE). For each subject, maximal isometric force (Fmax) and maximal rate of force development (RFDmax) were derived from the isometric strength tests and analyzed. Relative values were calculated to depict the topological structure of the tested muscle groups in relation to the general body strength and explosiveness. Statistical analysis revealed significant differences among all pairs (five pairs) of variables. In four pairs of variables (corresponding to four muscle groups), RFDmax demonstrated a higher topological influence compared to Fmax in overall body strength (iHG_L, iHG_R, iLE, and iDL). Conversely, one pair of variables showed the opposite effect.